Recent Progress in Contact Probing Methods of Two-Dimensional Materials and Van Der Waals Heterostructures - Zhang, Jiazhen; Chen, Peijian; Peng, Juan; Zhang, Yingying (Frontiers in Mechanical Engineering, 2022)
Due to the unique properties, two-dimensional materials and van der Waals heterostructures play an important part in microelectronics, condensed matter physics, stretchable electronics and quantum sciences. But probing properties of two-dimensional materials and van der Waals heterostructures is hard as a result of their nanoscale structures, which hinders their development and applications. Therefore, the progress of contact probing measurement in recent years including mechanical properties, interfacial properties, tribological properties, as well as electrical properties are summarized in this paper. It is found that useful properties such as Young's modulus, adhesive energy, friction coefficient and so on can be well estimated from contact probing methods. We believe that the contact probing methods will be more advanced to promote the blooming applications of two-dimensional materials and van der Waals heterostructures.